ANALISIS KESALAHAN BERBAHASA PADA KARANGAN DESKRIPSI SISWA KELAS XI SMK YPM 2 TAMAN - Sherly Faradita Saputri; Sunu Catur Budiono (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to describe the analysis of analysis of errors in the language description of students class XI smk ypm 2 park.Residered from the aspect of the contents of the essay, has not seen pouring ideas and ideas of students about the nature, images, and the real phenomenon of an object. In this case, the essay of the student can not be used as a means to represent lan gsung object so that the reader can not interpret and feel directly the object in the description. The phenomenon that occurs in learning writing essay writing description of students of class XI SMK YPM 2 Taman Sepanjang that the learning atmosphere of writing essay description less significant changes. Less effective learning atmosphere and fun for students, especially at the time of application of writing the text of the description text. This is stated based on the percentage of the value of writing ability description of the students of class XI SMK YPM 2 Taman Sepanjang. After conducting this research, the use of sentences is not effective in the description of students class XI SMK YPM 2 Park include: (1) the use of ineffective sentences consisting of the subject relationship with predicate, predicate with the object, and also the selection of words that are not appropriate (2) the use of sentences is not efficient, not sparing due to the use of words that have the same purpose, and also the use of unnecessary words, (3) the use of incoherent sentences, said to be unified if the subject and predicate, as well as description of aspects and elements the sentence is not in accordance with the Indonesian sentence pattern, other than that the sentence is not coherent also due to inappropriate relationship between sentences in paragraphs, (4) the use of the sentence is not careful, if the selection of words in the sentence is not in accordance with the intention to be conveyed.